PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA PERUSAHAAN ASURANSI DI BURSA EFEK INDONESIA - Melynda, Mira Dewi; Rasuli, M; Rokmawati, Andewi (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine the effect of corporate growth and capitalstructure on profitabiltias. to know the influence of company growth and capital structureto company value on insurence company, to know the influence of profitability tocompany value, to know the influence of profitability mediate growth of company tocompany value at Insurance Company at Indonesia Stock Exchange. And to know theeffect of profitabilty mediate capital structure to company value at Insurance Company atIndonesia Stock Exchange. The sampel of this study are 12 of 14 Population of InsuranseCompany that listed at Indonesia Stock Exchange. This study method is using purposivesampling and Data Analysis is using Path Anaysis. The results of this study indicate thecompanys growth and capital structure have a significant effect on profitability.Corporate growth and capital structure significantly influence the value of insurancecompanies in Indonesia Stock Exchange. Profitability significantly affects the value ofinsurance companies in Indonesia Stock Exchange. The Companys growth does affectthe value of the company through the profitability of insurance companies in theIndonesia Stock Exchange. Capital structure does affect the value of the companythrough the profitability of insurance companies in the Indonesia Stock Exchange.